PERAN DESA ADAT SANGEH DALAM PENGEMBANGAN WISATA SPIRITUAL DI DAYA TARIK WISATA PANCORAN SOLAS TAMAN MUMBUL - Anak Agung Mayun Widiastiti Utami; Nyoman Andika Kerta; Putu Milla Permatasari; Komang Dita Kusuma Anthara; I Made Krisnan Wijaya Putra; Cokorde Istri Dian Laksmi Dewi; Dumaria simanjuntak; Made Anggia Paramesthi Fajar (Jurnal Hukum Saraswati, 2024)
Spiritual tourism is one proof that tourism developed in Bali is tourism based on Balinese cultural tourism which is based on the teachings of the Hindu religion. The absence of complete and comprehensive regulations in regulating spiritual tourism in Bali that can provide protection for spiritual tourism objects places Traditional Villages in Bali and Balinese Customary Law as the front guard in protecting the preservation of cultural values, customs, religion and the village environment. local customs. The research used is an empirical legal research method. The approaches used to solve the problems in this research are the statutory approach (The statue approach), the Cultural Approach (The Culture Approach), and the Conceptual Approach (The Conceptual Approach). The role of the Sangeh Traditional Village is as the main character in developing spiritual tourism at the Pancoran Solas Taman Mumbul tourist attraction so its role is very strategic in promoting and managing the tourist attraction in order to improve the village economy, besides that the Sangeh Traditional Village must also play an active role in maintaining its sustainability. cultural values, customs and religion besides. Meanwhile, the role of customary law in developing spiritual tourism at the Pancoran Solas Taman Mumbul tourist attraction is as a controller of tourism flows. Customary law which is embodied in the form of traditional village awig-awig and pararem provides a sense of legal certainty in attitudes and actions, besides that it can also preserve the sacredness and preservation of the culture and nature of spiritual tourist attractions